Regulated recombinant protein production in the Antarctic bacterium Pseudoalteromonas haloplanktis TAC125. - RIPPA, VALENTINA; PAPA, ROSANNA; GIULIANI, MARIA; PEZZELLA, Cinzia; PARRILLI, ERMENEGILDA; TUTINO, MARIA LUISA; MARINO, GENNARO; DUILIO, ANGELA (Argelia Lorence, 2012)
This review reports results from our laboratory on the development of an effective inducible expression system for the homologous/heterologous protein production in cold-adapted bacteria. Recently, we isolated and characterized a regulative genomic region from Pseudoalteromonas haloplanktis TAC125; in particular, a two-component regulatory system was identified. It is involved in the transcriptional regulation of the gene coding for an outer membrane porin (PSHAb0363) that is strongly induced by the presence of l-malate in the growth medium. We used the regulative region comprising the two-component system located upstream the PSHAb0363 gene to construct an inducible expression vector – named pUCRP – under the control of l-malate. Performances of the inducible system were tested using the psychrophilic b-galactosidase from P. haloplanktis TAE79 as model enzyme to be produced. Our results demonstrate that the recombinant cold-adapted enzyme is produced in P. haloplanktis TAC125 in good yields and in a completely soluble and catalytically competent form. Moreover, an evaluation of optimal induction conditions for protein production was also carried out in two consecutive steps: (1) definition of the optimal cellular growth phase in which the gene expression has to be induced; (2) definition of the optimal inducer concentration that has to be added in the growth medium.